Keefektifan Model Pembelajaran Example Non-Example pada Pembelajaran Menulis Karangan Narasi Siswa Kelas VII SMP IT Nurul Ikhwah Kabupaten Nagan Raya - Siti Jahria Sitompul; Cut Nabilla Kesha; Agus Pratama; Desi Marlizar; Ilham Mirza Saputra; Syafrizal Syafrizal; Futri Syam (Indonesian Journal of Teaching and Teacher Education, 2022)
This study aims to determine the effectiveness of applying the example non example learning model in learning to write narrative essays in class VII students of SMP IT Nurul Ikhwah, Nagan Raya. The informants of this study were 20 female class VII students. The approach used in this study is a qualitative approach to the type of research, classroom action research (CAR). The design of PTK includes the steps of planning, action, observation, and reflection using two cycles. Data collection techniques used in this study were observation and tests. Observation or observation is a data collection method used to collect research data through observation and sensing. The test is a data collection instrument to measure students' abilities in cognitive aspects or the level of mastery of learning material. The use of examples non examples learning models is very effective in learning to write student narrative essays, in addition to higher student activity when the learning process takes place, student scores also increase after using the examples non examples learning model. This can be seen from the grade VII students of SMP IT Nurul Ikhwah who can meet the minimum completeness criteria which is higher than the assignment to write descriptive essays without using an example non example model. Before using the example non example model, there were 11 students out of 20 students who did not meet the minimum completeness criteria, after using the model, there were 3 students out of 20 who did not pass.